Participation of 414DDDD417 and 432KPAR435 in the thermostability of mercuric reductase isolated from the deep brine environment of atlantis II in the red sea - Eid, Ayman (AUC Knowledge Fountain, 2014)
Mercuric reductase (MerA) is an essential enzyme for the survival of microorganisms that reside in environments containing mercuric compounds. The enzyme converts the extremely toxic mercuric ions (Hg2+) into the less toxic volatile elemental mercury form (Hg0). A novel MerA molecule that has undergone multiple evolutionary adaptations to allow its host to cope with the harsh multiple abiotic stressors of the lower convective layer (LCL) of the Atlantis II (ATII) brine environment in the Red Sea has been recently characterized catalytically and structurally (JBC, 2014, 289,1675–1687). The brine pool at Atlantis II Deep covers an area of about 60 km2 and is located at a depth of 2000 to 2200 meters in the central region of the Red Sea. The LCL, the bottom layer of this pool, characterized by a unique combination of environmental conditions such as extreme salinity (26%), high temperature (68°C) and hydrostatic pressure, acidic pH (5.3), low light levels, anoxia, and high concentrations of heavy metals. The gene encoding this enzyme was identified in a metagenomic dataset established from microbial community resides in the LCL environment. The metagenome-derived MerA enzyme (ATII-LCL MerA) has simple and limited alterations in its primary structure relative to that of an ortholog from uncultured soil bacterium. Both enzymes are >91% identical and 67% of the substitutions in the ATII-LCL enzyme are acidic residues. The ATII-LCL molecule has also two short segments near the C-terminal, each containing two basic amino acids and a proline residue, here called box1 (432KPAR435) and box2 (465KVGKFP470). These alterations were found to reflect critical differences of the catalytic properties of the recombinants soil and LCL-ATII MerA enzymes. In contrast to the soil enzyme, the ATII-LCL enzyme is stable at high temperature, functional in high salt, resistant to high concentrations of Hg2+, and efficiently detoxifies Hg2+ in vivo. Site-directed mutagenesis of selected acidic residues showed direct effect on the halophilic nature of the enzyme, while replacement of the two boxes by the residues found in the soil ortholog reduced the degree of thermostability of the ATII-LCL enzyme. To better understand how the two boxes contribute to the thermostability of the ATII-LCL enzyme, we determined by homology modeling the 3D structure of the ATII-LCl and located acidic residues that potentially can establish ionic bonds with the basic residues located in the two boxes. An aspartic residue (D416) located within a stretch of four aspartic acids (414DDDD417) was found to have a potential proximity to be involved in an ionic bond with lysine 432 located in box1. Replacement of the four aspartic residues, 414DDDD417, by those found in the corresponding positions in the soil enzyme by site-directed mutagenesis was found to reduce the thermostability of the enzyme, while a triple mutant in which the two boxes and the four aspartic residues were mutated was found to have a thermostability comparable to the mesophilic soil enzyme. Thus, this work established that, in addition to the two boxes, the segment of the aspartic residues (414DDDD417) is a pivotal for full thermostability of the ATII-LCL MerA.